Overvoltages Transmitted in the Transformer Windings on the Lightning Impulse—An Analytical Method for Determination and Experimental Measurements - Maria-Cristina Nițu; Livia-Andreea Dina; Ileana-Diana Nicolae; Marian-Ştefan Nicolae; Paul-Mihai Mircea (Applied Sciences)
Overvoltages are brief and significant increases in the voltage level in an electrical system. They can be caused by a variety of factors, but the most common are associated with atmospheric discharges (lightning). When lightning strikes a power line, the resulting shock wave can induce surges in electrical equipment that is connected to that line, including transformers. The authors develop an analytical method in order to determine the maximum values of the overvoltages propagating in the transformer windings in case of lightning impulse. It is considered that the transmitted overvoltages consist of an inductive component (magnetic dispersion is neglected, as well as the energy exchange between the capacitances and inductances of the energized winding) and a capacitive component (between the energized winding and the receiving winding; in this case, the emphasis is on the energy exchange between the series capacitance and the inductance of the series winding). The proposed method was applied on a TTUS—ONAN/ONAF 31.5/40 MVA, 110/5/6.6 kV power transformer, and the obtained results were validated by experimental tests. The percentage error between the results obtained by modeling and the results obtained from transformer testing was less than 2%.